First Identification of Club Moss Use in Roman Britain - Gleba, Margarita; Foulds, Elizabeth M.; Teasdale, Al; Russ, Hannah (Archaeological Textiles Review, 2017)
Archaeological works undertaken as part of Highways England’s A1 road improvement scheme between Leeming Bar and Barton encountered a large rural Roman cemetery at Bainesse, near Catterick in North Yorkshire, United Kingdom. A copper-alloy bead was found to contain preserved string formed of two strands of an organic material twisted together in one of more than 200 burials. Scanning electron microscopy analysis suggests that the string was made of a club moss or a related species of fibre. This discovery further widens the repertoire of indigenous plant species used in Roman Britain for the production of textiles and emphasises the importance of fibre identification even of small organic remains.